2018
DOI: 10.1093/geroni/igy018
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Perceived Psychosocial Benefits of Senior Companion Program Participation Among Urban-Dwelling, Low-Income Older Adult Women Volunteers

Abstract: BackgroundAs the older adult population increases, it is imperative to increase older adults’ opportunities for social involvement, thus maintaining their important roles and contributions to society. While there are known health-related benefits of volunteerism among older adults, a dearth of information exists on the perceived benefits of volunteerism among low-income and ethnic minority older adults.PurposeTo understand the perceived psychosocial benefits of volunteering in the Senior Companion Program and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 59 publications
(83 reference statements)
3
10
0
Order By: Relevance
“…The results from this study concur with previous researchers’ findings examining the potential well-being benefits of volunteering in late life. Our results corroborate results from previous studies that have found positive effects, including a sense of accomplishment and belongingness in later life, among older adults who volunteer (Hood et al, 2018; Russell et al, 2019). In particular, our study showed that the level of purpose in life was higher among those who consistently participated in volunteer work.…”
Section: Discussionsupporting
confidence: 91%
“…The results from this study concur with previous researchers’ findings examining the potential well-being benefits of volunteering in late life. Our results corroborate results from previous studies that have found positive effects, including a sense of accomplishment and belongingness in later life, among older adults who volunteer (Hood et al, 2018; Russell et al, 2019). In particular, our study showed that the level of purpose in life was higher among those who consistently participated in volunteer work.…”
Section: Discussionsupporting
confidence: 91%
“…All rights reserved appreciated [7,8]. The results also complement qualitative research in which feeling appreciated and needed was found to facilitate a sense of purpose and accomplishment among older adult volunteers [32]. The present study extends these previous findings by linking appreciation to a broader range of psychological outcomes and thus highlights the importance of recognising the time, energy, skills, and resources volunteers contribute to their roles.…”
Section: Author Manuscriptsupporting
confidence: 82%
“…Despite a high level of resilience and strong connections to families of choice, older GBM can experience social isolation. Not only can volunteerism reduce social isolation and provide a sense of purpose, volunteering regularly has been associated with increased life satisfaction among older adults (Hood et al, 2018). Older GBM may lack opportunities or not feel welcome in mainstream organizations to contribute and volunteer.…”
Section: The Lived Experiences Of M/o-gbmmentioning
confidence: 99%